High Lithium Storage Performance of Co Ion-Doped Li4Ti5O12 Induced by Fast Charge Transport - Wang, M.; Chen, Y.; Yang, C. X.; Zeng, Y. H.; Fang, P. F.; Wang, W.; Wang, X. L. (Frontiers in Chemistry, 2022)
In this study, Co3O4 doped Li4Ti5O12 composites were designed and synthesized by hydrothermal reduction method and metal doping modification method. The microstructure and electrochemical performance of the obtained Co3O4 doped Li4Ti5O12 was characterized by XRD, SEM, TEM, EIS and galvanostatic tests. The results showed that Li4Ti5O12 particles attached to lamellar Co3O4 constitute a heterostructure and Co ion doped into Li4Ti5O12 lattice. This Co ion doped microstructure improved the charge transport ability of Li4Ti5O12 and inhibited the gas evolution behavior of Li4Ti5O12, which enhanced the lithium storage performance. After 20 cycles, the discharge specific capacity reached stable and the capacity retention maintained 99% compared with 20th cycle capacity after 1000 cycles at 0.1 A/g. It had excellent rate performance and long cycle stability, which the capacity reached 174.6 mAh/g, 2.2 times higher than that of Li4Ti5O12 at 5 A/g.